Legacies and change in polar sciences historical, legal and political reflections on the International Polar Year - Shadian, Jessica Michelle; Tennberg, Monica (Global interdisciplinary studies series, 2016)
Providing case study analyses of the politics of science in and around the International Polar Year of 2007-2008, this volume makes a distinct contribution to ongoing research focusing on the relationship between science, international politics, law and history. The contributors combine both interdisciplinary and multi-theoretical approaches to engage directly with the most recent debates in international relations scholarship, to include discussions of arctic climate change, governance issues, reflections on the Antarctic Treaty and the science-geopolitics interface amongst others. This is the first comprehensive account to look explicitly at the relationship between global politics and science through an account of the International Polar Years.